Do temperature surprise shocks in urban Canada lead to inflationary pressures? - Minger, Borys (Université d'Ottawa | University of Ottawa, 2023)
As the consequences of changing temperatures unfold with increasing severity in Canada, understanding the impact of climate change is critical. So far, no consensus has been reached on the magnitude or direction of the effects of temperature shocks. Using monthly data at the census metropolitan area (CMA) level, I create a novel Canadian shock series of the weighted average surprise of extreme temperature realizations in each quarter. I isolate the unexpected component of these weather events by controlling for the adjustments of expectations over time. My empirical analysis provides evidence that adverse temperature shocks lead to mostly deflationary pressures on the Canadian economy. These pressures are persistent, and primarily driven by cold shocks.